When Silence Speaks: Public Service Innovation, Village Authority, and the Negotiation of Traditional Justice in Rural Indonesia’s Youth Protection System - Erna Setijaningrum; Antun Mardiyanta; Bintoro Wardiyanto; Suhaimi Abd Samad (Social Sciences)
Rural Indonesian villages are defined by unique institutional dynamics in public service innovation, one of which manifests in juvenile justice administration where traditional governance meets modern legal structures. These institutional arrangements position villages as sites of public service innovation at the intersection of competing normative orders, especially regarding youth protection standards and cultural practice maintenance. We address patterns of public service innovation and institutional adaptation in rural juvenile justice systems through the systematic analysis of practices across five villages in East Java. Through consolidating stakeholder interviews and justice proceeding observations, our analysis shows how communities innovate in public service delivery by negotiating between formal requirements and informal mechanisms while integrating distinctive legal traditions and maintaining institutional legitimacy across multiple domains. The examination identifies two central patterns in public service development. First, processes of normative integration emerge through systematic institutional synthesis where communities innovate service delivery approaches while preserving cultural coherence. Second, these innovation processes correspond to variations in resource distribution, traditional authority configurations, and state presence across geographic and social contexts. We document how unspoken institutional practices and innovative service arrangements shape justice negotiations between community and state spheres, particularly in mediating youth protection within traditional normative frameworks of public service delivery.